2014
DOI: 10.5380/rf.v45i2.35164
|View full text |Cite
|
Sign up to set email alerts
|

RELAÇÃO DA MORFOMETRIA E COMPETIÇÃO COM O CRESCIMENTO DE Trichilia claussenii EM UM FRAGMENTO DE FLORESTA SEMIDECIDUAL, RS

Abstract: Este trabalho teve como objetivos determinar a relação de variáveis morfométricas e de índices de competição com o crescimento em diâmetro de Trichilia claussenii, em um fragmento da Floresta Estacional Semidecidual na região central do Rio Grande do Sul. Os dados utilizados neste estudo foram obtidos de 29 árvores amostradas por classe diamétrica, denominadas árvores centrais, com diâmetro à altura do peito (d) igual ou superior a 10,0 centímetros, distribuídas em 51 parcelas permanentes, totalizando 0,51 hec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 10 publications
1
8
0
4
Order By: Relevance
“…These authors reported that the increment decreases with increasing competition and with higher basal area per hectare. This effect was also observed by Silveira et al (2015), who observed the existence of association between competition and increase in Trichilia claussenii C. DC. diameter, concluding that the greater the competition, the lower the tree growth.…”
Section: Density Factorsupporting
confidence: 77%
“…These authors reported that the increment decreases with increasing competition and with higher basal area per hectare. This effect was also observed by Silveira et al (2015), who observed the existence of association between competition and increase in Trichilia claussenii C. DC. diameter, concluding that the greater the competition, the lower the tree growth.…”
Section: Density Factorsupporting
confidence: 77%
“…Independentemente da idade, as médias do formal de copa não foram influenciadas pelos espaçamentos de plantio. A média desse formal foi de 0,47±0,13, indicativo de copa esbelta (FC < 1) conforme Orellana e Koehler (2008) e Silveira et al (2015). Indivíduos menores em altura tiveram maior formal de copa (r = -0,29; p ≤ 0,01); o DAP não se correlacionou com o formal de copa (r = -0,08; p > 0,05).…”
Section: Resultsunclassified
“…Geralmente, as intervenções silviculturais se baseiam na manipulação da competição ou dos fatores que a influenciam para orientar o desenvolvimento das árvores (PEER et al, 2017;SILVEIRA et al, 2015). Inicialmente, busca-se um espaçamento de plantio que possibilite o máximo crescimento a um menor custo (MARTINS et al, 2009).…”
unclassified
“…Canopy morphometry studies through the crown area (CA), formal of crown (FC) and crown proportion (CP), associated the crown diameter and length to other variables in the same stand (FIGUEIREDO et al, 2014). Because it is a vital organ, normally correlated to its growth in diameter (SILVEIRA et al, 2015) and height (SANTOS et al, 2015a), these indices (e.g. CA, FC and CP) are more indicative of competition effect.…”
Section: Introductionmentioning
confidence: 99%